Does My Body Offend You? - Cuevas, Mayra; Marquardt, Marie F., 1972- (New York : Alfred A. Knopf, 2022)
"A timely story of two teenagers who discover the power of friendship, feminism, and standing up for what you believe in, no matter where you come from."--Provided by publisher.
Keywords: Teenage girls -- Juvenile fiction; High school students -- Juvenile fiction; Dress codes -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Teenage girls -- Fiction; High school students -- Fiction; Dress codes -- Fiction; Friendship -- Fiction; Orange Park (Fla.) -- Juvenile fiction; Orange Park (Fla.) -- Fiction; Young adult fiction